(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2026)
Interprofessional Education (IPE) is an educational approach designed to develop collaborative competencies among health profession students to improve the quality and safety of healthcare services. Various learning methods implemented in IPE may contribute differently to students’ collaborative skill development. This study aimed to compare the effectiveness of roleplay and case discussion methods on collaborative competence among health students. A quantitative study using a one-group repeated measures design was conducted among 86 health students selected through simple random sampling. All participants experienced both learning methods, namely case discussion and roleplay-based scenarios. Collaborative competence was measured using the Interprofessional Collaborative Competency Attainment Survey (ICCAS). Data were analyzed using the Wilcoxon Signed Rank Test. The results showed that the mean ICCAS score following roleplay (4.36 ± 0.62) was slightly higher than that following case discussion (4.35 ± 0.62); however, the difference was not statistically significant (p = 0.367). These findings indicate that both roleplay and case discussion have relatively comparable effectiveness in facilitating the development of collaborative competencies among health students. Therefore, either method can be implemented as an alternative strategy in IPE according to learning objectives and educational contexts.